Assess Nurses’ Job Satisfaction and Marital Quality - Bander Mohammed Qassim; Tahani Nail Alanazi; Zaid Ali Abdullqader Elaqi; Sarab Jaber Ahmad Maghawi; Samyah Mohamed Hassan Harshan; Masoud Ali Masoud Alshahrani; Saad Hassan Saad Aljadrani; Fatma Menahi Mohammed Alqahtani; Sarhan Ali Abdullah Alsaloli; Aziza Mohammed Alsultan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The nursing workforce faces persistent challenges, including job dissatisfaction, high turnover rates, and stress, which negatively impact healthcare outcomes. Previous research has indicated a potential link between marital status and job satisfaction, but little is known about how marital quality, specifically, affects job satisfaction among nurses. This study aimed to explore the relationship between marital quality and job satisfaction among married female nurses, considering the role of sociodemographic factors. Methods: A descriptive correlational study was conducted using a web-based survey distributed to 2,296 married female nurses from tertiary hospitals. Participants were employed full-time for at least one year and were in their first marriage. Data were collected on demographics, marital quality, and job satisfaction. Marital quality was measured using the Chinese Marital Quality Inventory, and job satisfaction was assessed using the Chinese Nurses Job Satisfaction Scale. Statistical analyses included descriptive statistics, t-tests, Pearson correlation, and linear regression. Results: The overall response rate was 71.6%. A moderate positive correlation (r = 0.63, p < 0.05) was found between marital quality and job satisfaction. Factors such as age, monthly income, average daily hours spent with a spouse, and marital quality were identified as significant predictors of job satisfaction. Nurses with higher marital quality, higher income, and more time spent with their spouses reported greater job satisfaction. Conclusion: This study suggests that marital quality is positively correlated with job satisfaction among married female nurses. Addressing factors such as marital quality and work-life balance could improve job satisfaction and potentially reduce turnover rates in nursing. Further research is needed to explore these relationships in different cultural and professional contexts.